2008
DOI: 10.1177/0954008308093254
|View full text |Cite
|
Sign up to set email alerts
|

A Deep-Blue Electroluminescence from 2,5-Diphenyl-1,3,4-oxadiazole and Polyfluorene Copolymer End-capped with Triphenylamine

Abstract: An electron-transporting 2,5-bis(4-bromophenyl)-1,3,5-oxadiazole (OXD) was incorporated by copolymerization into polyfluorene (PF) end-capped with a 4-bromo-4',4"-dimethyltriphenylamine (TPA) main chains on the Yamamoto coupling method to improve the initial electroluminescence (EL) color stability against applied voltage and the device operation lifetime. The copolymer, PF/OXD-TPA, possessed a high molecular weight enough for film-forming ability and excellent solution-processability, that is, good solubility… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 17 publications
1
3
0
Order By: Relevance
“…This hypothesis is also supported from a previous result where a PF terminated with hole-transporting triphenylamine (TPA) units displays significantly improved color stability [8,15]. We also reported that the incorporation of controlled contents of electrontransporting 2,5-diphenyl-1,3,4-oxadiazole units into the TPA-terminated PF main chains through copolymerization allowed further improvement of the color stability [16]. The oxidative degradation also strongly depends on the device encapsulation techniques for complete air insulation.…”
Section: Introductionsupporting
confidence: 83%
“…This hypothesis is also supported from a previous result where a PF terminated with hole-transporting triphenylamine (TPA) units displays significantly improved color stability [8,15]. We also reported that the incorporation of controlled contents of electrontransporting 2,5-diphenyl-1,3,4-oxadiazole units into the TPA-terminated PF main chains through copolymerization allowed further improvement of the color stability [16]. The oxidative degradation also strongly depends on the device encapsulation techniques for complete air insulation.…”
Section: Introductionsupporting
confidence: 83%
“…For such purpose, poly(1,3,4-oxadiazole)s are of great interest due to the electron-withdrawing character of the 1,3,4-oxadiazole ring that can facilitate the injection and transport of electrons. 11 We considered it interesting to synthesize two series of polyimides and copolyimides containing both oxadiazole and naphthalene units in the main chain, so that the resulting polymers have better thermal and thermooxitative stability and efficient photoluminescent and electron-transporting properties for future use in polymer lightemitting diodes. In this study, we investigated their thermal stability and photo-optical properties.…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, the 1,3,4-oxadiazole rings are promising chemical moieties for introduction into the polymer backbone or in the pendant structure due to the electron-withdrawing character of the 1,3,4-oxadiazole ring that can facilitate the injection and transport of electrons. 28 Therefore, the light-emitting ability of these polymers containing oxadiazole and naphthylimide chromophores was assessed on the basis of the photoluminescence spectra which were recorded for polymer solutions in NMP after excitation with UV light of different wavelengths.…”
Section: Resultsmentioning
confidence: 99%